Soil Carbon-to-Nitrogen Ratio Can Predict the Grassland Biodiversity-Productivity Relationship Evidence From Local, Regional, and Global Scales - Zhang, Hongjin (Global change biology, 2025)
© 2025 John Wiley & Sons Ltd.